The Carpentier-Edwards Perimount Magna mitral valve bioprosthesis: intermediate-term efficacy and durability. Issue 1 (December 2016) - Loor, Gabriel; Schuster, Andres; Cruz, Vincent; Rafael, Aldo; Stewart, William; Diaz, James; McCurry, Kenneth
Abstract Background The Carpentier-Edwards Perimount Magna mitral valve bioprosthesis (Edwards Lifesciences, Irvine, CA) is a low-profile version of the earlier Perimount valve that uses the ThermaFix process for enhanced calcium removal. The Magna valve has been in use since 2008, yet no publication, until now, has verified its intermediate-term safety and efficacy. Methods From 2008 through 2011 (our 4-year study period), 70 Magna valves were implanted in the mitral position at a single institution (the Cleveland Clinic). Echocardiograms were prospectively interpreted. For this study, we reviewed patients' charts; endpoints included hemodynamic measurements, in-hospital morbidity and mortality, valve-related events, resource utilization, and 5-year survival rates. Results The mean patient age was 68 years; 43 % of the patients had New York Heart Association (NYHA) class III or IV disease, and 51.4 % had moderately severe, or worse, mitral regurgitation (MR). For 43 % of the patients, the Magna valve implantation was a reoperation. For 83 %, the Magna valve implantation also included a concomitant cardiac procedure. The median survival rate was 4.7 years and 90 % of patients were free from significant structural valve degeneration at 5 years. Preoperative atrial fibrillation, ischemic MR, intraaortic balloon pump placement, cardiogenic shock, cardiac arrest, and renal failure were associated with increased mortality. Right ventricular systolic pressure decreased from 50 mmHg preoperatively to 40 mmHg postoperatively, according to our matched-pair analysis (P = 0.003) . Per their final echocardiogram during our study period, 98 % of surviving patients had trivial or no MR, one patient had mild MR, and one patient had severe MR. Conclusions Our 5-year experience indicates that the Magna valve offers excellent intermediate-term durability and substantial echocardiographic improvement; its low-profile design make it ideal for reoperations and for concomitant cardiac procedures, including valve replacement.